Language in Education Policy at the Local Level: Ideologies and Practices - Paudel, Jnanu Raj (KMC Journal, 2026)
Language in education policy is a contested issue in multilingual nations like Nepal. Policy makers in these contexts face the dual challenge of incorporating the demands of ethnic and linguistic identity through multilingual education, with the desire for global language learning through English Medium Instruction (EMI). Against this backdrop, this paper aims to identify the language ideologies of local level authorities and teachers in the process of local level policy formation in Nepal to understand how these actors navigate the inherent tensions between multilingual education (MLE) and EMI policy demands. Using a phenomenological research design, I draw on the first-hand experience of local-level officers and teachers through interviews and FGDs. Local level authorities lack knowledge of the need for medium of instruction polices and have not yet approved medium of instruction policies for their region. However, during the interviews and discussions, local authorities appear to be guided by a neoliberal ideology that supports standard and global language above local indigenous and minoritized languages for education. However, school teachers are against the imposition of a language policy that prioritizes a single language over others. Teachers wish to be given agency to decide on the language to be used in the classroom based on the learning needs of their students. The study therefore offers implications for TESOL professionals and policy makers on the need for policies that balance the global role of English with support for linguistic diversity and teacher agency.